Biomassa Vegetal, Estoque de Carbono e Dinâmica em um Fragmento de Floresta Ombrófila Mista Montana - Martins, Patrikk John (2011)
The goals of this work were to characterize the phytosociology and dynamics of a Mixed Rain Forest in the city of Boa Ventura do São Roque, Paraná State; to adjust and select allometrics models for the estimation of aboveground biomass and carbon; assess the carbon content of 12 arboreal species and its components; compare the carbon content of the species with the conversion factor of 50%; and evaluate the ecological grouping influence over the species` carbon fixation capacity. This work was divided into three chapters. The first one described the phytosociology and dynamics of the studied forest. Data was collected between the years 2007 and 2009, from permanents samples. The second chapter reports the adjust and selection of the equations used to predict the aboveground biomass of the whole tree and its components (stem, bark, alive branches, dead branches and foliage). Twenty models were tested for this study commonly used in the literature. For the adjustment of the equations, the least squares` method was applied, and the selection of the best equations was based on the statistics such as the adjusted coefficient of determination (R? adj), standard error of the estimate (Syx%) and graphics analysis of the residues distributions. The predictions for the whole tree and other components (stem, alive branches, foliage) did not get good results. The best results for the carbon estimation in the tree`s components were found in the bark and dead brunches. For the other components and whole tree the results were not expressive. On the third chapter, the statistical analysis did not shown differences at 5% of probability, among the carbon content found in the trees` components. Comparing the 12 species, there were difference only between Nectandra lanceolata, which presented the highest carbon content mean (45,06%), and Cestrum sp., which got the lowest carbon content mean (41,77%). The comparison between the carbon content means, found for all the evaluated species, and the 50% conversion factor widely used, showed that the conversion factor super estimates the carbon content in the trees at a average rate of 14,27%, generating values not representatives of the tree carbon fixation capacity.